1977
DOI: 10.1071/ar9770011
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects at three development stages on the yield of the wheat ear

Abstract: Temperature effects on the growth and yield of wheat (cv. Gamenya) were studied in controlled environments under three day/night temperature regimes (viz. 25/20, 20/15 and 15/10°C) and at three stages of development, viz. vegetative, ear development and grain growth stages. The most important temperature effects were found during the ear development phase. Plants grown at low temperature at this time had long culms, large flag leaves and more potentially fertile florets in each spikelet. The number of florets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
58
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 0 publications
7
58
1
Order By: Relevance
“…Under rainfed condition, the highest HI was assigned to genotype G8 (72.10%) followed by genotypes G34 (65.59%) and G4 (62.41%) and the lowest HI was observed in genotype G21 (25.16%) followed by genotypes G1 (37.41%) and G29 (38.99%). Warrington et al (1977) explained that drought stress at anthesis may lead to yield loss by reducing TKW and if accompanied with high temperatures after anthesis, accelerates whole plant senescence and reduces biological yield and HI. Bayoumi et al (2008) and Dorostkar et al (2015) observed that grain yield, biological yield, HI and TKW decreased under stress condition.…”
Section: Analysis Of Variancementioning
confidence: 99%
“…Under rainfed condition, the highest HI was assigned to genotype G8 (72.10%) followed by genotypes G34 (65.59%) and G4 (62.41%) and the lowest HI was observed in genotype G21 (25.16%) followed by genotypes G1 (37.41%) and G29 (38.99%). Warrington et al (1977) explained that drought stress at anthesis may lead to yield loss by reducing TKW and if accompanied with high temperatures after anthesis, accelerates whole plant senescence and reduces biological yield and HI. Bayoumi et al (2008) and Dorostkar et al (2015) observed that grain yield, biological yield, HI and TKW decreased under stress condition.…”
Section: Analysis Of Variancementioning
confidence: 99%
“…At the ear development stage (double ridge to anthesis), yield reduction caused by heat stress is mainly due to the decrease of grain number per unit area (Owen 1971;Warrington et al 1977;Saini and Aspinall 1982;Fischer 1985;Wardlaw et al 1989). At the grain growth stage (anthesis to maturity), heat stress is divided into two types according to Wardlaw et al (2002): chronic stress (20-32°C) and heat shock (>32°C).…”
mentioning
confidence: 99%
“…Growing irrigated (Evans and Wardlaw 1976) and water use wheat requires the application of large efficiency(BeggandTurnerl9T6),butonly amounts of N fertilizer to obtain maximum in a few cases were the interacting effects of yields. The effect of N and moisture on the all three variables examined in one experigrowth, grain yield and protein content of ment (Hutcheon and Rennie 1960;Sosulski wheatdependsontheweather,especiallythe et al 1966; Partridge and Shaykewich temperature (Warrington et al 1977;Evans 1972). In none of the latter studies was a and Wardlaw 1976).…”
mentioning
confidence: 99%